Cultivation of Public Security Talents in Police Colleges and Universities Under the Holistic Approach to National Security - Keyan, Luo (Pacific International Journal, 2024)
This research delves into the formulation of a training model for nurturing talent capable of comprehending and addressing the complex spectrum of public security challenges. The study reexamines traditional pedagogies and underscores the integration of multidisciplinary approaches and practical skill sets. Utilizing a mixed-method research design, it entails a survey of academic curricula, in-depth faculty interviews and analysis of case studies.Findings illuminate the exigencies of enhancing strategic thinking, legal acumen, and crisis management abilities among students.The proposed training model accentuates the fusion of theoretical knowledge with application, encompassing network security proficiency, international law, and emergency response strategies.The outcomes envisage a more dynamic and resilient approach to police education, aligning with contemporary political security imperatives.